Recommendations Guidance Services for Developing Self-Regulated Learning for Adolescent Students: Systematic Review of Literature - Supriani, Sri Agus (Academia Edu Cendekia Indonesia (AEDUCIA), 2023)
Adolescents with good self-regulation skills can easily control and regulate themselves cognitively, emotionally, and behaviorally. They will complete their developmental tasks obediently, disciplined, and comply with existing rules. In addition, they will not play truant, will not create riots, and will not be late in completing their tasks. This research uses a systematic literature review method with a qualitative approach. This method aims to discover, evaluate, and interpret research results related to a particular research question, subject, or phenomenon of interest. This research's results illustrate that classical and group guidance services are considered effective interventions for students in self-regulated learning research. In the ten-year research period, there is much research on self-regulated learning in middle school to high school or teenage students.